Cooperative Study: Implementation of Human Rights In Indonesia and Finland - Dela Natalia Siallagn; Abelia Rahma Ananda; Najeela Luthfiyah Muhammad (Journal of Law, Politic and Humanities, 2026)
This study explores the implementation of human rights in Indonesia and Finland through a comparative perspective. The research focuses on identifying the factors that influence the effectiveness of human rights enforcement in both countries, including institutional strength, law enforcement practices, human resources, legal socio-culture, and cultural environment. Although both countries possess comprehensive legal frameworks, their implementation differs significantly. In Indonesia, challenges such as inconsistent law enforcement, limitations in human resources, and cultural environment that may conflict with human rights principles contribute to weaker implementation. In contrast, Finland establishes a more stable system supported by strong institutions, high levels of public trust, and social values that reinforce legal compliance, despite facing challenges related to minority protection and law enforcement practices. This study aims to provide a deeper understanding of how structural and societal factors shape the realization of human rights in different national contexts.